The Antigenicity of Epidemic SARS-CoV-2 Variants in the United Kingdom - Wu, Jiajing; Zhang, Li; Zhang, Yue; Wang, Haixin; Ding, Ruxia; Nie, Jianhui; Li, Qianqian; Liu, Shuo; Yu, Yongxin; Yang, Xiaoming; Duan, Kai; Qu, Xiaowang; et al. (Frontiers in Immunology, 2021)
To determine whether the neutralization activity of monoclonal antibodies, convalescent sera and vaccine-elicited sera was affected by the top five epidemic SARS-CoV-2 variants in the UK, including D614G+L18F+A222V, D614G+A222V, D614G+S477N, VOC-202012/01(B.1.1.7) and D614G+69-70del+N439K, a pseudovirus-neutralization assay was performed to evaluate the relative neutralization titers against the five SARS-CoV-2 variants and 12 single deconvolution mutants based on the variants. In this study, 18 monoclonal antibodies, 10 sera from convalescent COVID-19 patients, 10 inactivated-virus vaccine-elicited sera, 14 mRNA vaccine-elicited sera, 9 RBD-immunized mouse sera, 4 RBD-immunized horse sera, and 4 spike-encoding DNA-immunized guinea pig sera were tested and analyzed. The N501Y, N439K, and S477N mutations caused immune escape from 9 of 18 mAbs. However, the convalescent sera, inactivated virus vaccine-elicited sera, mRNA vaccine-elicited sera, spike DNA-elicited sera, and recombinant RBD protein-elicited sera could still neutralize these variants (within three-fold changes compared to the reference D614G variant). The neutralizing antibody responses to different types of vaccines were different, whereby the response to inactivated-virus vaccine was similar to the convalescent sera.